Asset-Liability Management of Maybank During 1991-1997 - Dass, a/l Velaisamy (1998)
This study sought to analyze the assets and liabilities management in banking with a focus on the experience of Maybank which is one of the leading banks in Malaysia. The liabilities and asset structure of this as reflected in its balance sheets for the period of 1991-1997 have been examined as a case study. The study is data based. It is primarily based on balance sheet statements of Maybank which is incorporated in its annual reports. With a scrutiny of these annual reports we used a quantitative approach in analysing the significance of major variables such as deposits, credits, investment, loan and among others to see how asset and liability of the bank is managed. Specifically some ratios and percentages have been computed to see how the bank managed its business to achieve its diverse goals of profitability and liquidity in order to win the confidence and trust of its customers and public at large in the country. The findings on this study shows that Maybank’s asset and liability are well managed and it is economically performing well in banking business. Despite the present dismal economic situation in the country, the bank has managed to make some profit around RM0.50 million in 1997-1998(June End). In the next millennium the bank need to prepare for still better strategies to meet the new challenges.